THE EFFECT OF USING THE JARIMATIKA METHOD AND THE PYTHAGOREAN MULTIPLICATION TABLE ON SOLVING MATHEMATICAL CONCEPTS OF MULTIPLICATION OPERATIONS - Rini, Triana Sulistya; Nur Sofianto, Eko Wahyu; Irawati, Ratna Kartika (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2025)
This study aims to determine the effect of students' numeracy skills by using the jaritmatika method and the Pythagorean multiplication table on student learning outcomes significantly in mathematics lessons on student multiplication operations. The method used in this research is the quasi experimental method of experimental research which is basically the same as cause-and-effect research but is carried out using pseudo-experimental methods. This research was conducted at SDN Sungai Jingah 5 with saturated sampling of grade III. The results showed that the numeracy skills of experimental grade students using the jaritmatika method and tables can be seen from the average results of 82.13 are in the